2018
DOI: 10.1111/1747-0080.12475
|View full text |Cite
|
Sign up to set email alerts
|

Re‐evaluating the nutritional awareness, knowledge and eating behaviours of women attending a tertiary maternity hospital following iterative service redesign

Abstract: Aim Since the opening of the new Mater Mothers' Hospital in 2008, innovative initiatives were developed, implemented and evaluated to meet women's nutritional needs. This study evaluated changes in women's nutritional awareness, knowledge and behaviours and compared these data with our baseline survey. Methods During 2014–2017, 421 postnatal women were surveyed across nine survey periods. Results were compared with those from our 2008 survey (n = 102). Surveys assessed nutrition knowledge, attitudes, behaviour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 50 publications
(119 reference statements)
0
13
0
Order By: Relevance
“…Significant positive associations were evident between health factor scores, maternal age and education. Analysis suggests that women of the cohort were more motivated to make healthy dietary choices with advancing age and increasing education, conclusions supported by contemporary research in a comparative population . As such this data may indicate the presence of a nutrition literacy deficit in young women of this cohort, particularly those who have not undertaken a tertiary education .…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Significant positive associations were evident between health factor scores, maternal age and education. Analysis suggests that women of the cohort were more motivated to make healthy dietary choices with advancing age and increasing education, conclusions supported by contemporary research in a comparative population . As such this data may indicate the presence of a nutrition literacy deficit in young women of this cohort, particularly those who have not undertaken a tertiary education .…”
Section: Discussionmentioning
confidence: 54%
“…Analysis suggests that women of the cohort were more motivated to make healthy dietary choices with advancing age and increasing education, conclusions supported by contemporary research in a comparative population . As such this data may indicate the presence of a nutrition literacy deficit in young women of this cohort, particularly those who have not undertaken a tertiary education . Appropriate dietetic interventions in these women have the potential to influence the development of life‐long dietary behaviours for both themselves and their children …”
Section: Discussionmentioning
confidence: 91%
“…Despite the absence of data to compare GWG across the three cohorts, we are able to draw on self-reported data from a smaller population from the same study period to provide a proxy measure of the interventions’ effectiveness [25]. In this paper examining women’s service engagement, health behaviours and GWG across 2014–17 (n421) with a cohort of women surveyed at the opening of the MMH in 2008 (n102) we were able to demonstrate that the proportion of women experiencing correct GWG increased from 23.2 to 38.6% (with excessive GWG decreasing from 57.3 to 32.6%), p < 0.001 [25]. We noted the significant increase in women gaining weight within the recommended IOM guideline ranges was a very promising outcome which was lower than many recent studies that used similar methodologies (E.g.…”
Section: Discussionmentioning
confidence: 99%
“…38% [26], 39% [27], 42% [28], 47% [4], and 52% [29]). Furthermore, we demonstrated that a greater proportion of women accessed the nutrition services in 2014–17 compared with 2008 (19.7% vs 9.9%) and rated nutrition resources provided and/or viewed favourably (> 3.5 out of 5) [25].…”
Section: Discussionmentioning
confidence: 99%
“…The evidence suggests that many pregnant women have limited knowledge of healthy diet and required physical activity in pregnancy ( de Jersey et al, 2013 ; Wilkinson et al, 2018 ). This is a serious concern as more than half of all women, in developed countries, gain excess weight in pregnancy ( Goldstein et al, 2018 ) and excessive weight gain is linked a number of adverse pregnancy outcomes such as gestational diabetes ( Barton et al, 2015 ; Goldstein et al, 2017 ), pregnancy related hypertension ( Macdonald-Wallis et al, 2013 ) and macrosomia (excessive infant size) ( Heery et al, 2013 ), which predisposes to childhood obesity.…”
Section: Introductionmentioning
confidence: 99%